2019
DOI: 10.3390/cryst9090470
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Liquid Crystals: Physics and Applications

Abstract: Electrooptic modes with fast response and high contrast ratio are highly desirable in modern photonics and displays. Ferroelectric liquid crystals (FLCs) are especially promising for fulfilling these demands by employing photoalignment technology in FLC cells. Three electrooptic modes including surface stabilized FLC (SSFLC), deformed helix ferroelectric (DHF) mode, and electrically suppressed helix (ESH) mode are reviewed with the corresponding electrooptic effects like bi- and multi-stable switching, continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…The new liquid crystals materials are highligthed for display and photonics applications [2], including (i) fast high resolution LC display devices, such as field sequential color ferroelectric LCD [3]; (ii) LC sensors [2]; (iii) LC lenses [4]; (iv) LC E-paper devices, including electrically and optically rewritable (ORW) LC E-paper and security films [5]; (v) photo induced semiconductor quantum rods alignment for new LC display applications [6]; (vi)100% polarizers based on photoalignment [7]; (vii) LC smart windows with voltage controllable transparency [8]; (vii) LC antenna elements with a voltage controllable frequency and direction of radiation [9]. Special attention should be paid to photoalignment technology which will be a key technology in the nearest future.…”
Section: New Trends In Lc Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…The new liquid crystals materials are highligthed for display and photonics applications [2], including (i) fast high resolution LC display devices, such as field sequential color ferroelectric LCD [3]; (ii) LC sensors [2]; (iii) LC lenses [4]; (iv) LC E-paper devices, including electrically and optically rewritable (ORW) LC E-paper and security films [5]; (v) photo induced semiconductor quantum rods alignment for new LC display applications [6]; (vi)100% polarizers based on photoalignment [7]; (vii) LC smart windows with voltage controllable transparency [8]; (vii) LC antenna elements with a voltage controllable frequency and direction of radiation [9]. Special attention should be paid to photoalignment technology which will be a key technology in the nearest future.…”
Section: New Trends In Lc Technologymentioning
confidence: 99%
“…Usual thickness of azo-dye layer is about 10-15 nm, which make them very cheap and efficient for LC alignment. Photoalignment enables to solve many problems of FLC [3]: (i) mechanical stability, no defects; (ii) avoiding of FLC domains for a high spontaneous polarization; (iii) optimal anchoring energy with a very high contrast ratio; (iv) wide viewing angles; (v) very high resolution and fast response time.…”
Section: Photoalignment Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…For the last few decades, self-assembling materials represent a fascinating area of dynamic research, which provides a highlighted approach for design of new structures with predefined functionality [ 7 , 10 , 11 , 12 , 13 ]. Chiral smectic liquid crystalline (LC) materials belong to one of the most exciting classes of such organic materials that are able to self-assemble in a polar layered structure of nanometer scale [ 11 , 13 , 14 , 15 , 16 , 17 , 18 ]. The self-organization structure of such compounds, and hence their favorable electro-optic, structural, and dielectric properties, can be adjusted by a proper design of molecular architecture build up from various units [ 15 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The simulated results showed that the sensitivity could reach as high as 9.164 MHz/(V/m) and the smallest resolution was 0.1115 V/m. Dr. Qi Guo et al reviewed three electrooptic modes including surface stabilized ferroelectric liquid crystals, the deformed helix ferroelectric mode, and electrically suppressed helix mode [7]. The general operation principles…”
mentioning
confidence: 99%